The Political Economy of the US Mortgage Default Crisis - Mian, Atif; Sufi, Amir; Trebbi, Francesco (American Economic Review, 2010)
We examine the effects of constituents, special interests, and ideology on congressional voting on two of the most significant pieces of legislation in US economic history. Representatives whose constituents experience a sharp increase in mortgage defaults are more likely to support the Foreclosure Prevention Act, especially in competitive districts. Interestingly, representatives are more sensitive to defaults of their own-party constituents. Special interests in the form of higher campaign contributions from the financial industry increase the likelihood of supporting the Emergency Economic Stabilization Act. However, ideologically conservative representatives are less responsive to both constituent and special interests. (JEL D72, G21, G28)